Nutritional status and associated factors among adolescent girls attending high schools in Jigjiga, Ethiopia - Mahamed Abdulahi Ahmed; Abdulkarim Mohamed Ali; Shamsedin Mahdi Hassan; Hassen Mahamed Jerar (Clinical Nutrition Open Science, 2025)
Summary: Adolescent schoolgirls' nutritional status and dietary habits are crucial indicators of their current and future health outcomes. This study assessed the sociodemographic, socio-economic, nutritional status, dietary patterns, physical activity, lifestyle, and health conditions of 148 schoolgirls in the Somali Region, Ethiopia. A structured questionnaire and anthropometric measurements were used to collect data. Descriptive statistics were applied for data analysis. The study found that 14.9% of the schoolgirls were undernourished based on their Body Mass Index (BMI), indicating a significant public health concern. Furthermore, 58.8% of respondents reported experiencing significant weight fluctuations in the past year, and only 52% consumed three meals per day, while 35.1% skipped breakfast. Fruit and vegetable consumption was low, with only 32.4% consuming them daily. Fast food consumption was high (69.6%), with sanbusa being the most common. Physical inactivity was prevalent, with 50% of respondents reporting no engagement in physical activity during the week, and 78.4% not participating in organized sports. About 31.1% consumed carbonated and energy drinks daily, while 66.2% reported experiencing pre-menstrual syndrome. Knowledge, attitude, and practices around nutrition were mixed: only 15.5% claimed to have a lot of knowledge about the nutritional value of food, and while 93.2% recognized nutrition's importance for health, 39.2% felt they lacked adequate information about healthy eating. The findings reveal critical nutritional and lifestyle challenges among schoolgirls, including undernutrition, low dietary diversity, high fast-food and sugary drink consumption, limited physical activity, and insufficient dietary knowledge. These results underscore the need for targeted interventions to promote healthier eating habits, increase nutrition education, and encourage physical activity among adolescent girls to improve their overall health and well-being.